Push out bond strength of resin -based endodontic sealer loaded with silver gold nanoparticles in vitro study - Nermine Hassan; Mona Riad; Shereen Hafez Ibrahim; Bassam Ahmed Abulnoor; Reham Hassan (BDJ Open)
Abstract Objectives The push-out bond strength to the intraradicular dentin was evaluated in this in vitro study using an epoxy-based endodontic sealer loaded with silver-gold nanoparticles. Additionally, the benefits of using the nanoparticles as a canal pretreatment before applying the sealer were evaluated in comparison to using the sealer alone. Methodology After being decoronated and instrumented, thirty extracted human central incisors were obturated and then divided horizontally into three parts (coronal, middle, and apical) with a thickness of 2 mm. Three groups of slices were created at random: Groups I (control) and II received AH Plus sealer, AH Plus sealer loaded with silver gold nanoparticles, and III received nanoparticles as a pretreatment for the canal prior to gutta-percha and AH Plus sealer for obturation. The specimens were loaded at a rate of 0.5 mm/min utilizing a Universal Test Machine and put through a push-out test. Statistics were applied to each data collection. Additionally, the significance level was set at P ≤ 0.05. Results A push-out test showed that the groups differed significantly from one another. The tested groups differed significantly in both the coronal and middle portions, with group (II) exhibiting the highest push-out strength values. Group (II) had the highest push-out strength values in the apical portion (3.66 ± 0.72), followed by group (III) (2.90 ± 1.45), while group (I) had the lowest value (2.88 ± 1.73). There was no significant difference between the groups. Conclusions the experimental AH Plus sealer combined with silver-gold nanoparticles demonstrated the most effective adhesion followed by nanoparticles as a canal pretreatment prior to sealer application when compared to AH Plus sealer alone.